WHAT SHOULD A PROFESSIONAL TEACHER BE LIKE? (The Role of Exact Sciences in the Era of Modern Development, 2024)
The article discusses the attitudes of teachers towards knowledge, skills, and teaching practices. It also provides important information regarding what students studying in the field of pedagogy should prioritize in order to become qualified professionals in the future. This research highlights the essential factors necessary for successful performance as a teacher.